Bioinformatic and metabolomic analysis reveals miR-155 regulates thiamine level in breast cancer. Issue 2 (28th February 2015) - Kim, Sinae; Rhee, Je-keun; Yoo, Hyun Ju; Lee, Hee Jin; Lee, Eun Ji; Lee, Jong Won; Yu, Jong Han; Son, Byung Ho; Gong, Gyungyup; Kim, Sung Bae; Singh, Shree Ram; Ahn, Sei Hyun; et al.
Highlights microRNA-155 is an oncogenic miRNA involved in various types of tumors. Bioinformatic analysis and metabolic-profiling data revealed a positive correlation between miR-155 and thiamine level. We found that miR-155 regulates thiamine metabolism through SLC19A2, SLC25A19, and TPK1 genes. We found a positive correlation between miR-155 and thiamine level in triple negative breast cancer. Our findings suggest that miR-155 plays a crucial role in breast cancer metabolism.